The Effect of Job Security and Burnout on Turnover Intention Mediated by Job Satisfaction - Chelsia Ernes; Yohana F Cahya Palupi Meilani (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The high rate of turnover among healthcare workers has become a big challenge, particularly during the COVID-19 pandemic. Therefore, understanding the factors associated with turnover intention is important. The objective of this study is to analyse the effect of job security, burnout, and their impact on turnover intention mediated by job satisfaction in healthcare workers. This study is a quantitative survey with a cross-sectional approach and 155 respondents of healthcare workers who worked in a private hospital in Batam during the COVID-19 pandemic were taken as the sample using a purposive sampling method. Online questionnaires were distributed in order to collect the data. PLS-SEM analysis method is used to analyse the data. The findings from this study are job security has a positive and significant effect on job satisfaction, burnout has a negative and significant effect on job satisfaction, job satisfaction has a negative and significant effect on turnover intention, and job satisfaction is proved as a significant mediator towards turnover intention. This finding has implications for hospital managers to make recommendations that will enable the hospital to retain more health workers and thus reduce the turnover rate.Keywords: Job security, Burnout, Job satisfaction, Turnover intention